PHBMT1, a BAHD-family monolignol acyltransferase, mediates lignin acylation in poplar. Issue 2 (22nd November 2021) - de Vries, Lisanne; MacKay, Heather A; Smith, Rebecca A; Mottiar, Yaseen; Karlen, Steven D; Unda, Faride; Muirragui, Emilia; Bingman, Craig; Vander Meulen, Kirk; Beebe, Emily T; Fox, Brian G; Ralph, John; et al.
Abstract: Poplar ( Populus ) lignin is naturally acylated with p -hydroxybenzoate ester moieties. However, the enzyme(s) involved in the biosynthesis of the monolignol– p -hydroxybenzoates have remained largely unknown. Here, we performed an in vitro screen of the Populus trichocarpa BAHD acyltransferase superfamily (116 genes) using a wheatgerm cell-free translation system and found five enzymes capable of producing monolignol– p -hydroxybenzoates. We then compared the transcript abundance of the five corresponding genes with p -hydroxybenzoate concentrations using naturally occurring unrelated genotypes of P. trichocarpa and revealed a positive correlation between the expression of p -hydroxybenzoyl-CoA monolig-nol transferase ( pHBMT1, Potri.001G448000) and p -hydroxybenzoate levels. To test whether pHBMT1 is responsible for the biosynthesis of monolignol– p -hydroxybenzoates, we overexpressed pHBMT1 in hybrid poplar ( Populus alba × P. grandidentata ) ( 35S::pHBMT1 and C4H::pHBMT1 ). Using three complementary analytical methods, we showed that there was an increase in soluble monolignol– p -hydroxybenzoates and cell-wall-bound monolignol– p -hydroxybenzoates in the poplar transgenics. As these pendent groups are ester-linked, saponification releases p -hydroxybenzoate, a precursor to parabens that are used in pharmaceuticals and cosmetics. This identified gene could therefore be used to engineer lignocellulosic biomass with increased value for emerging biorefinery strategies. Abstract : An enzyme from poplar, p -hydroxybenzoyl-CoA monolignol transferase ( pHBMT1 ), adds ester-linked p -hydroxybenzoate moieties to lignin that can be readily hydrolyzed to release the aromatic compound.